(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work aimed to bring an analysis of the protection of personal data in consumer relations based on the existing legal mechanisms addressing the sources between the data protection systems (the LGPD-General Data Protection Law) and the protection consumer protection (the CDC-Consumer Protection Code). Such analysis, started from the point that, today, we live in a world characterized by the great amount of information released on the world wide web and the most varied ways in which these personal data are used. Still, considering the recognition of the protection of personal data as a fundamental right, based on the decision of the STF, which suspended the effectiveness of MP 954/2020 and endorsed the violation of the constitucional right to privacy, privacy and confidentiality of data; PEC 17/2019, which, after its approval, will grant the protection of personal data the constitucional status of fundamental right to all Brazilian citizens; and, Law n. 13.709/2019 – General Law for the Protection of Personal Data-LGPD, although this reference in its text to fundamental rights does not present personal data as such, it only provides for the processing of said data. It is concluded that the recognition of the protection of personal data as a fundamental right is essential to consecrate to all Brazilians, not only in the physical sphere but also in the digital sphere, respect for citizenship and the dignity of the human person in all segments, here specifically, in consumer relations in a Democratic Rule of Law.